2015
DOI: 10.1166/jnn.2015.10740
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Open-Circuit Voltage of Phenyl C61-Butyric Acid Methyl Ester-Like Based Bulk-Heterojunction Solar Cells

Abstract: New materials are currently being sought for use in active layers of bulk-heterojunction organic solar cells, and computational modeling plays an important role in this search. Although open circuit voltage (V(oc)) is one of the fundamental quantities that determine the efficiency of a solar cell, there is no consensus on the best way to estimate this magnitude for new materials from calculations of the electronic structure. In this paper, we compare ways of predicting V(oc) values employing a diverse group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…As can be seen, the smallest deviations obtained for both E HOMO and E LUMO were with the PBE functional (below 10%). This result is in agreement with previous studies, where the PBE functional has shown good results for fullerene derivatives in comparison with experimental data [30][31][32][33]. Thus, we decided to conduct our studies using the DFT/PBE/6-311G(d,p) methodology.…”
Section: Methodssupporting
confidence: 90%
“…As can be seen, the smallest deviations obtained for both E HOMO and E LUMO were with the PBE functional (below 10%). This result is in agreement with previous studies, where the PBE functional has shown good results for fullerene derivatives in comparison with experimental data [30][31][32][33]. Thus, we decided to conduct our studies using the DFT/PBE/6-311G(d,p) methodology.…”
Section: Methodssupporting
confidence: 90%